Classical Hodgkin's lymphoma masquerading as Riedel's thyroiditis. Issue 2 (28th February 2022) - Young, Kenneth Stuart; Cunniffe, Harriet A; Ali, Zahabia; Nassif, Ramez
Abstract : We present the case of a 38-year-old woman with a progressively tender swelling of the thyroid gland, who was treated as Riedel's thyroiditis based on two fine needle aspirations and a core biopsy. She was later found, on partial thyroidectomy, to have nodular sclerosis classical Hodgkin's lymphoma.